Pridevniške tvorjenke na -ski, -ški, -čki in -cki v Trubarjevih in Dalmatinovih prevodih biblijskih besedil - Legan Ravnikar, Andreja (Slavia Centralis, 2020)
Adjectival derivatives with the suffixes -ski, -ški, -čki and -cki in Trubar's and Dalmatin's translations of biblical textsThis paper analyses the most productive model of forming adjectival derivatives used in the 16th century: derivation with the suffix -ski and its variant -ški, and with the suffixes -čki and -cki which are affixed to the same word-formation base. The paper is an attempt to identify the competitive relations between these suffixes and discern the differences between Primož Trubar and Jurij Dalmatin with regard to their use. The paper also attempts to shed light on the complex issue of forming literary neologisms in the16th century.
Keywords: 16th century; Bible translations into Slovene; adjectival derivatives with the suffixes -ski, -ški, -čki and -cki; Primož Trubar; Jurij Dalmatin